Legal Study of The Differences in The Application of Article 2 and Article 3 of The Correspondence Law in Market Development Corruption Cases (Case Study of Decision Number 33/PID.SUS-TPK/2025/PT SMG) - Bagas Adi Priyoga; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2026)
Introduction:Corruption is an extraordinary crime that disrupts legal stability, the economy, and public trust in the government. Because it comprises distinct elements, namely unlawful acts and abuse of authority, Articles 2 and 3 of the Corruption Eradication Law are often interpreted differently in Indonesia's law enforcement system.Method: In this normative legal research, a case approach is used which is derived from secondary data such as court decisions, laws and regulations, books and scientific journals collected through literature review and descriptive analysis.Novelty: This research differs from previous research, namely, examining the judge's considerations in the market development corruption case with an emphasis on the differences in how Article 2 and Article 3 of the Corruption Law are applied.Objective: This study aims to see how judges consider Article 2 and Article 3 of the Corruption Law, as well as the legal consequences of the differences in the application of the two articles in the corruption case of the construction of the Kedungwuni Market, Block F, Pekalongan Regency, which was decided under Number 33/PID.SUS-TPK/2025/PT SMG.Results: Research shows that the panel of judges applied Article 3 of the Corruption Eradication Law because the defendant's actions more closely resembled abuse of authority in carrying out his duties as a project supervisor, resulting in state financial losses. The legal interpretation of the differences in the application of the two articles relates to differences in the elements of proof, the type of criminal liability, and the potential penalties imposed on the perpetrator.Conclusion: Therefore, consistency is needed in the interpretation and application of these two articles in order to create legal certainty and fair law enforcement in criminal acts of corruption.